Influence of rosmarinic acid and Salvia officinalis extracts on melanogenesis of B16F10 cells - Oliveira,Karina B. (2013)
Melanin is a photoprotective skin pigment, and pathologies characterized by hypo or hyperpigmentation are common. New compounds that regulate melanogenesis are, therefore, opportune, and many natural products with this property, as polyphenols, have been described. Salvia officinalis L., Lamiaceae, is a widely used food spice that contains high amounts of phenol derivates, including rosmarinic acid. The aim of this work was to evaluate the contribution of rosmarinic acid in the melanogenic activity of sage extracts. Fluid and aqueous extracts of sage and purified rosmarinic acid were assayed for B16F10 cytotoxicity and, then, evaluated on melanin production and tyrosinase activity. While sage extracts showed a concentration-dependent ability to significantly increase melanin production without necessarily changing the enzymatic activity, rosmarinic acid showed a dual behavior on melanogenesis, increasing melanin biosynthesis and tyrosinase activity at low concentrations and decreasing it at higher levels. Rosmarinic acid may collaborate with sage extracts activity on melanogenesis, although other compounds may be involved. This is the first time that a dual action of rosmarinic acid on melanogenesis is reported, which may be useful in further studies for therapeutic formulations to treat skin pigmentation disorders.